2022
DOI: 10.1021/acs.orglett.2c01801
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enantioselective Reductive Cross Coupling of Electron-Deficient Olefins

Abstract: We report an enantioselective reductive cross coupling of electron-deficient olefins. Using a visible-light-driven cooperative photoredox and chiral Brønsted acid-catalyzed reaction with a Hantzsch ester as the terminal reductant, various cyclic and acyclic enones with 2-vinylpyridines were converted in high yields (up to 93%) to a wide range of enantioenriched pyridine derivatives featuring diverse γ-tertiary carbon stereocenters with good to excellent enantioselectivities (up to >99% ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The reaction demonstrated good enantioselectivity with up to 93% ee and high yields, reaching up to 97% yield. This was accomplished through a tandem radical conjugate addition and enantioselective protonation process using various hydrocarbons and silanes (40) reacting with different α-branched 2-vinylazaarenes (39). The reaction employed TBADT (PC-6) as a photocatalyst and (S)-SPINOL-based CPA-12 or -13 as a hydrogen bonding catalyst, enabling the desired outcomes.…”
Section: Cpa Joint Tbadt Photocatalystmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction demonstrated good enantioselectivity with up to 93% ee and high yields, reaching up to 97% yield. This was accomplished through a tandem radical conjugate addition and enantioselective protonation process using various hydrocarbons and silanes (40) reacting with different α-branched 2-vinylazaarenes (39). The reaction employed TBADT (PC-6) as a photocatalyst and (S)-SPINOL-based CPA-12 or -13 as a hydrogen bonding catalyst, enabling the desired outcomes.…”
Section: Cpa Joint Tbadt Photocatalystmentioning
confidence: 99%
“…The reaction displayed high yields (up to 93%) and yielded pyridine derivatives with diverse γ-tertiary carbon stereocenters, exhibiting good to excellent enantioselectivities (up to > 99% ee). (Scheme 31) [39] Jiang's team have successfully developed an enantioselective intermolecular [3 + 2] cycloaddition reaction of N-arylcyclopropylamines (91) with 2-aryl acrylates/ketones (92) in 2023. This breakthrough was achieved through the employment of a cooperative photoredox and chiral hydrogen bonding catalysis strategy.…”
Section: The Enantioselective Synthesis Using Cpa and Dpzmentioning
confidence: 99%
“…In addition to the [2 + 2] cycloaddition, it was also possible to conduct a reductive cyclization to obtain monocyclic products in the presence of a Hantzsch ester (HEH) as a reductant. , Notably, we found that the dual and hybrid catalyst systems showed reactivity patterns different from those observed in the [2 + 2] cycloaddition (Table ). 1a was reacted in the presence of HEH and MS5A in toluene under irradiation with a 427 nm LED.…”
mentioning
confidence: 92%
“…Pyridine-based scaffolds are indispensable among pharmaceutically relevant small molecules, and methods for their derivatization are mainstays in the medicinal synthetic toolkit. , Many strategies toward the synthesis of substituted pyridines have been developed, employing both ring-building and derivatization approaches. However, many of these methods cannot introduce stereochemical information, as is the case with most azine C–H functionalization , and cross-coupling strategies . Pyridines’ ligand functionality has long stymied the development of metal-catalyzed methods, and when asymmetric methods are successful, control over the new stereocenter is usually confined to proximal α- or β-positions. Strategies to access γ-stereoenriched pyridines are substantially more rare, relying on the asymmetric addition of prochiral radicals into vinylpyridines. As drug discovery ventures into three-dimensional space, more diverse methods will be required to access these sp 3 -rich molecules with high selectivity rapidly . Our group envisioned that a biocatalytic method could impart control over constructing a remote pyridyl γ-stereocenter from readily available α-halopyridines, efficiently increasing the complexity of simple heterocyclic structures.…”
mentioning
confidence: 99%